Effects of Dexmedetomidine Combined with Intravenous Anesthesia on Oxidative Stress Index, Postoperative Sleep Quality, and Brain Function in HICH Patients. (19th March 2022) - Shi, Jiong; Zhao, Guangping; Liu, Panpan; Bai, Yuwei; Chen, Yongxue
Abstract : To investigate the effects of dexmedetomidine combined with intravenous anesthesia on oxidative emergency indicators, postoperative sleep quality, and brain function in patients with hypertensive cerebral hemorrhage (HICH), a total of 285 HICH patients admitted to our hospital from February 2020 to February 2021 were selected. The combined anesthesia group ( n  = 142) and the control group ( n  = 143) were established by the random number table method. The control group received conventional intravenous anesthesia, and the combined anesthesia group received dexmedetomidine combined intravenous anesthesia. Two groups of patients before and after operation was observed vital signs, oxidative stress index difference, comparing each time, the change of the two groups of brain function index, adverse reactions occurred between observation group, and the postoperative period of Pittsburgh Sleep Quality Index Scale (PSQI) score as a result, the Pearson correlation coefficient analysis of oxidative stress level and the correlation of HICH patients sleep quality. After operation, the mean arterial pressure (MAP) and heart rate (HR) of patients in both groups decreased significantly. The MAP level in the combined anesthesia group significantly increased compared to the control group, and the HR level decreased significantly than the control group (all P < 0.05 ). The levels of TNF- α, IL-6 and MDA in both groups increased significantly on day 7 after operation compared with before operation, but the indexes in the combined anesthesia group significantly decreased compared with the control group (P < 0.05 ). The level of superoxide dismutase (SOD) in both groups significantly decreased compared to that before operation, and the index value in combined anesthesia group significantly increased compared to that in the control group (P < 0.05 ). After surgery, the levels of central nerve specific protein (S100- β ) and neuron specific enolase (NSE) in 2 groups increased with time, and the indexes in the combined anesthesia group significantly decreased compared to the control group (all P < 0.05 ). The incidence of adr in combined anesthesia group decreased significantly than that in control group (P < 0.05 ). After surgery, PSQI scores of the two groups showed a downward trend with time extension, and scores of the combined anesthesia group decreased significantly than those of the control group at 24 h, 48 h and 7 d after surgery (all P < 0.05 ). Pearson's correlation coefficient was used to analyze that TNF- α, IL-6, and MDA levels were positively correlated with PSQI score, while SOD level was negatively correlated with PSQI score (all P < 0.05 ). Dexmedetomidine combined with intravenous anesthesia can significantly improve the vital signs and oxidative stress response of HICH patients, effectively reduce the risk of adverse reactions, have little impact on the brain function of patients, and can improve the postoperative sleep quality of patients. This operation is worthy of clinical application. In addition, this study further analyzed the influence mechanism of postoperative sleep quality in patients with HICH and showed that TNF- α, IL-6, MDA, and SOD were all correlated with sleep quality in patients with HICH, suggesting that follow-up detection of these indicators has positive significance in improving the prognosis of patients.